Representations of gender in public rhetoric. The case of law-making on immigration in the Greek parliament - Thanopoulou, Maria; Tsiganou, Joanna (The Greek Review of Social Research, 2016)
This article intends to investigate the way in which gender stereotypes, even when latent, are so potent that manage to emerge, leaving their gender inscription on social issues publicly debated in neutral terms. Even in cases of competing political actors representing different fragments of the political spectrum, these stereotypes are actually reproduced identically. They frame in the same way the public speech of politicians regardless of their gender. These arguments are evidenced in the case of law-making on immigration in Greece through the examination of the relevant parliamentary debates. In fact, the analysis of the debate on a single legal provision concerning the issuing of work permits to foreign artists is proven more than adequate for understanding the ways in which social representations on gender are implicated in public rhetoric.